Կաթողիկոսական աթոռի տեղափոխության խնդրի շուրջ (Ե. դար) - Արփինե Չանթիկյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Первой из приписываемых Овану Первому Мандакуни реформ является перенесение патриаршего престола. В арменоведении существуют противоречивые взгляды и точки зрения о периоде перевода патриаршего престола из Вагаршапата в Двин. В данной статье мы попытались аргументировать нашу позицию, согласно которой анализ исторических свидетельств и упоминаний позволяет нам думать, что патриарший престол был перенесен в годы Католикоса Ована Первого Мандакуни, когда Вардан Мамиконян после своей славной победы стал марзпаном (наместником) Армении и получил право на некую свободу действий. The first among the reforms ascribed to Hovhan I Mandakuni is the relocation of the Catholicosate. There are contradictory and conflicting opinions and viewpoints in the Armenian studies on the precise date of the relocation of the Catholicosate from Vagharshapat to Dvin. With this article we have tried to substantiate our standpoint, according to which the analysis of historical quotations and testimonies enables to think that the Catholicosate was relocated during the Pontificate of Catholicos Hovhan I Mandakuni, when Vahan Mamikonyan, after his glorious victories, became the governor of Armenia and gained some freedom of action.
Keywords: Christianity; History of the Armenian Church